Loess deposits in the Tajik Basin, Central Asia: chronology, provenance and palaeoclimatic implications since the Last Glacial. (27th October 2020) - Tian, Shengchen; Sun, Jimin; Zhang, Zhiliang; Abdulov, Sherzod; Cao, Mengmeng; Gadoev, Mustafo; Oimahmadov, Ilhomjon
Abstract : The thick loess deposits in Tajikistan are important archives for palaeoclimatic reconstruction in Central Asia during the Quaternary. To date however, adequate high‐resolution studies of chronology and climatic evolution of the Tajik loess have still not been carried out. In this paper, chronology, dust provenance, and palaeoclimatic significance of a loess section in the centre of the Tajik Basin has been studied. Optically stimulated luminescence (OSL) dating yields ages ranging from ~60.8 to 0.8 ka, indicating that this loess section accumulated during the Last Glacial period and the Holocene. The provenance of the Tajik loess includes dust transported by westerly winds from the upwind deserts in Turkmenistan, and minor proximal particles derived from alluvial sediments of the nearby mountains and fluvial/glacifluvial deposits on the river flood‐plains. Multiple palaeoclimatic proxies including colour, particle size, environmental magnetic parameters, and element concentrations together with their correlation with the deep‐sea δ 18 O record suggest that the Tajik loess accumulated during cold and dry stadial periods, while palaeosols formed during warm and moist interglacials or interstadials, which is similar to the Chinese Loess Plateau. Although the two regions have different dust provenances and wind systems, such similarity indicates that the palaeoclimatic variations in both regions might be forced by a common global factor, e.g. the global ice volume. Variations in global ice volume influenced the climate in Tajikistan and the Loess Plateau through affecting the westerlies and the East Asian Monsoon, respectively.